Effect of graphic element type on visual perceptions of curvilinear and rectilinear flow diagrams. Issue 2 (3rd April 2018) - Branch, Robert Maribe; Mané, C. Erika; Shin, Min Young
Abstract: This study replicated a study conducted by Branch, Rezabek and Cochenour (1998) who contended that perception and interpretation can be influenced by the type of graphic elements used to compose a diagram. Because instructional design conditions resemble complex situations that require learning development systems sufficient to address the diversity and variety of actions required for the successful operation of intentional learning environments. The idea of matching the concomitant complexity of a process with the inherent complexity within a specific context is consistent with the law of requisite variety, which contends that in order to properly facilitate the quantity and diversity of a situation, you must have the ability to generate an equal quantity and diversity of responses. Instructional designers who utilize process models to generate teaching and learning materials will find the results of this study valuable as they consider effective ways to visualize flow diagrams intended to convey complex content. This study is relevant and important to the visual literacy as it seeks to answer the question: Do varieties of flow diagrams conveying similar content stimulate similar viewer perceptions? This study confirmed the results of the original 1998 study indicating that diagrams conveying similar flow patterns elicit similar adjectives.